Xenotransplantation: from proof of concept to clinical reality (Swiss Medical Weekly, 2025)
Organ allotransplantation remains the gold standard for treating end-stage organ failure, yet the chronic shortage of donor organs limits access to life-saving therapy. Xenotransplantation, particularly the use of genetically modified pigs as organ donors, has emerged as a viable alternative, supported by decades of preclinical research and recent breakthroughs in gene editing and immunosuppressive protocols.The current era of solid organ xenotransplantation began in 2021 with studies involving human recipients who were brain dead and has since progressed to the transplantation of porcine hearts, kidneys, and a liver into living patients. While initial cases were complicated by significant comorbidities and short-term survival, recent xenotransplants in carefully selected patients have yielded improved outcomes. Notably, one recipient of a porcine kidney recently passed the six-month post-transplant mark, an important milestone for the field. Regulatory momentum is also building. In 2025, the U.S. Food and Drug Administration approved clinical trials led by United Therapeutics and eGenesis targeting patients with end-stage kidney disease.The upcoming 18th Congress of the International Xenotransplantation Association, to be held in Geneva, Switzerland, from 30 September to 3 October 2025, underscores the global relevance of the current breakthrough. Geneva has historic ties to the field, having hosted key early policy discussions and managed the International Human Xenotransplantation Inventory for over a decade. As xenotransplantation moves into a new clinical era, continued collaboration as well as ethical and regulatory oversight will be essential to guide its safe and effective implementation.